Compliance with Quality Guidelines in Hiv Anti-Retroviral Interventions (Art) Interventions at Kisii Teaching And Referral Hospital - Ayamo, George O. (JOOUST, 2020)
The goal of Antiretroviral Therapy/Treatment (ART) is to reduce morbidity and mortality among people living with HIV (PLHIV) hence improve their health. Use of ART also contributes to preventing new HIV infections. To achieve this goal, ART implementing programs need to comply with the relevant Ministry of Health guidelines by ensuring ART services adhere to set standards. There have been concerns regarding adherence to the Ministry of Health guidelines regulating implementation of ART interventions and the effect of compliance or lack of it on HIV treatment outcomes. This was a descriptive retrospective and prospective study conducted at Kisii Teaching and Referral Hospital (KTRH) to assess compliance with Ministry of Health guidelines to determine the quality of ART program implementation at the hospital. The study sought to; identify structural factors influencing compliance with guidelines on ART service quality, investigate compliance with guidelines in ART clinical services delivery, and assess viral suppression levels of PLHIV as a measure of quality of ART treatment outcomes. The study examined file data of 367 PLHIV sampled from files of PLHIV who received ART services at KTRH in 2019 and assessed compliance performance of select quality of care indicators against recommendations of ARV guidelines. Qualitative data on structural factors affecting compliance in service delivery was collected through key informant interviews with health care providers. Quantitative data was analyzed using Statistical Package for Social Sciences and summarized using descriptive methods including mean, median, percentages and results presented in graphs, charts, and tables. The results of the quality indicators assessed showed the mean compliance level (73.9%) with the guidelines was significantly below the expected (100%) (t=3.038, p=0.014). Results of analysis of Health Care Providers’ (HCP) perceptions regarding ART services compliance with quality guidelines also showed significantly low compliance level (68%) against the expected 100% (t=6.971, p<0.001). Assessment of the facility structural factors revealed glaring gaps regarding structural inadequacies relating to human resource availability, training, physical infrastructural capacity, critical laboratory and pharmaceutical supplies. Based on the findings, the study concludes there was weak compliance with the guidelines on use of Antiretroviral Drugs for Treating and Preventing HIV Infection in Kenya (2018) in the delivery of critical clinical ART services at KTRH, which could negatively affect health outcomes for PLHIV. The study has recommended to the hospital management measures to address the identified compliance gaps.
Keywords: Anti Retroviral Therapy; Data Quality Assessment; Health Care Interventions